Ciudad Virtual: Una aplicación para conectar a pequeños comerciantes con sus clientes potenciales (2023)
This document presents the Virtual City business model, an application designed to solve the connection problem that exists between small merchants of products or services and their potential customers. Two groups of users were defined: buyers who don't have time to get what they need, and sellers who want to grow their business; In both cases, they are presented with a value proposition that solves their pain. Finally, empathy processes with users and experiments were carried out, which allowed the design of a minimum viable product that reflects feasibility for the continuity of the business idea.